One-shot transcatheter double valve replacement: six-month follow-up—a case report. Issue 6 (14th November 2020) - Lutter, Georg; Salem, Mohamed; Frank, Derk; Puehler, Thomas
Abstract: Background: Transcatheter aortic valve replacement (TAVR) in combination with a valve-in-valve (V-i-V) transcatheter mitral valve replacement (TMVR) is a rare procedure in comparison to surgical therapy especially in young patients. We report on a young patient at high surgical risk, receiving a double valve implantation with two S3 transcatheter heart valves. Case summary: A 59-year-old female patient with two previous mitral valve replacements due to endocarditis and re-endocarditis experienced a new onset of severe mitral valve stenosis in combination with progredient aortic stenosis. She was admitted to the hospital with severe dyspnoea and intermittent non-invasive ventilation [New York Heart Association (NYHA) III–IV]. An interventional transapical transcatheter double valve implantation was planned and carried out due to cardiac decompensation and high comorbidity preoperatively (STS score of 6.92). At 6-month follow-up, the patient presented herself in an improved condition with reduced symptoms (NYHA I–II), a good functional status of both valves and an advanced right and left ventricular function in the echocardiogram. Discussion: Even in younger patients at high risk, a combined native TAVR and V-i-V TMVR procedure can be performed. In this case, a transcatheter SAPIEN 3 valve was transapically implanted with good clinical mid-term outcome at 6 months.